MXene / phenolic aldehyde-based carbon fiber film as well as preparation method and application thereof

By introducing MXene and Fe ions into the phenolic fiber raw wire, MXene/phenolic carbon fiber film with high gas sensitivity was prepared, which solved the problems of difficulty in preparing the existing phenolic resin-based carbon fiber film gas sensors and low gas sensitivity, and achieved efficient gas response effect.

CN119843422APending Publication Date: 2025-04-18ZHONGYUAN ENGINEERING COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510261411.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing phenolic resin-based carbon fiber membrane gas sensor is difficult to prepare and has low gas sensitivity, making it difficult to improve its gas responsiveness without affecting the spinning properties of the phenolic resin.

Method used

MXene and Fe ions were used to introduce into the phenolic fiber raw wire, and MXene/phenolic carbon fiber film was prepared by dry spinning and carbonization processes, and the gas-sensitive characteristics were improved by using the high specific surface characteristics of MXene and the active site effect of Fe.

Benefits of technology

The response value of the phenolic carbon fiber film to NO2 gas is significantly improved, and the response value is increased by 3-4 times, and it works at room temperature, reducing power consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843422A_ABST
    Figure CN119843422A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of gas sensors, discloses an MXene / phenolic aldehyde-based carbon fiber film as well as a preparation method and application thereof, and aims to solve the technical problems that a phenolic aldehyde-based gas sensor is difficult to prepare and low in gas sensitivity. The preparation method comprises the following steps: preparing a high-ortho phenolic aldehyde stock solution from phenol and aldehyde compounds under the action of a catalyst; the preparation method comprises the following steps: mixing high-ortho phenolic aldehyde with a solution containing MXene and ferric acetate, and carrying out dry spinning to prepare nascent fibers; and (3) pressing and carbonizing the nascent fiber to obtain the carbon fiber film. And coating an electrode on the film, and combining a circuit and a test system to obtain the gas sensor. The prepared sensor is simple in structure, light in weight and flexible, and can work at room temperature; the response value to NO2 gas is increased by 3-4 times by utilizing the gas-sensitive characteristic of the MXene and doped iron-reinforced phenolic-based carbon fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of gas sensor preparation, and in particular to a method for preparing a gas sensor based on a MXene / phenolic carbon fiber film. Background Art

[0002] Gas sensors are highly specialized detection devices that play a vital role in many fields, including industrial safety, environmental monitoring, medical health, and smart homes. Semiconductor-based gas sensors are a common type of gas sensor, which have the advantages of simple production, low cost, high sensitivity, and fast response. They are currently widely used. However, the commonly used metal semiconductor gas sensors have a high operating temperature and require additional current heating to maintain the operating temperature. Carbon-based films have good semiconductor properties and certain gas sensitivity, and can work at room temperature, thereby reducing power consumption. However, carbon-based sensors have disadvantages such as low response values ​​and slow response recovery speeds, which have prevented them from being widely used.

[0003] Phenolic acid is a polymer material prepared from phenol and aldehyde compounds, which has excellent flame retardant properties. Phenolic acid itself has a high carbon content and can be used to make carbon-based materials. However, the phenolic resin conventionally prepared from formaldehyde and phenol is not easy to spin into fibers due to its high degree of crosslinking, and its texture is brittle after carbonization and its flexibility is not good enough. At present, it is often assisted by adding easy-to-spin polymer materials to form fibers. This method has high costs and affects the flame retardancy, mechanical properties, carbon content and other problems of phenolic acid itself. The previous research of this research group, CN108930095A, has disclosed a method for preparing a high-ortho-thermosetting phenolic resin-based hollow nano gradient activated carbon fiber membrane. In this patent, a high molecular linear polymer needs to be used as a spinning aid. At the same time, the electrospinning method has high process parameter requirements and is not easy to be doped with inorganic materials for co-spinning.

[0004] MXene is an excellent two-dimensional material with high specific surface area and other characteristics, which is suitable for improving the gas-sensitive properties of materials. However, how to introduce it into phenolic resin solution without affecting the spinnability of phenolic resin and further improve the gas sensitivity of phenolic resin-based carbon-based fiber membrane is still a difficult problem. Summary of the invention

[0005] In view of the technical problems that phenolic resin-based carbon fiber film gas sensors are difficult to prepare and have low gas sensitivity, the present invention proposes a MXene / phenolic resin-based carbon fiber film and a preparation method and application thereof.

[0006] To achieve the above object, the technical solution of the present invention is implemented as follows:

[0007] A method for preparing a MXene / phenolic carbon fiber film, comprising the following steps:

[0008] (1) A mixed phenol containing p-ethylphenol (the mass ratio of phenol to p-ethylphenol is (8-9):1) is mixed with a mixed aldehyde (a mixture of formaldehyde and 5-hydroxyvaleraldehyde) and a divalent metal catalyst in a reactor, heated and stirred until boiling (90-98°C) and then continued to react for 2-7h, then an acidic catalyst is added and continued to react for 1-4h, and then vacuum distilled at a heating temperature of 105-135°C to remove water and small molecular organic matter. The polymer remaining in the reactor is a high ortho-phenolic resin, and naturally cooled to room temperature. In the present invention, a mixed phenol containing p-ethylphenol is used instead of phenol as a raw material. Since the ethyl group in p-ethylphenol occupies the para position, the active sites on the benzene ring are reduced, and the para position is prevented from participating in the polymerization reaction, thereby reducing crosslinking. On the one hand, the 5-hydroxyvaleraldehyde in the raw material improves the flexibility of the molecular chain and increases the spinnability. On the other hand, its tail hydroxyl group can form a non-covalent bond with the metal ion and the oxygen-containing functional group on the surface of MXene, which is beneficial to increase the viscosity of the spinning solution, thereby facilitating spinning.

[0009] (2) Mix MXene and ferric acetate in ethanol in a certain proportion and stir evenly to obtain a mixed solution A; mix the prepared high-ortho-phenolic resin with the mixed solution A, heat to 75-88°C and stir to react for 2-3.5h, then add an amine curing agent and heat to 80-92°C to react for 0.5-1h before dry spinning to obtain nascent fibers. Among them, MXene is an excellent two-dimensional material with characteristics such as high specific surface area, which is suitable for improving the gas-sensitive properties of materials. The use of Fe ions, on the one hand, forms non-covalent bonds with hydroxyl groups on the surface of MXene, which is beneficial to the gelation of MXene, and on the other hand, as a metal element, it can improve gas sensitivity.

[0010] (3) Fiber carbonization: The primary fibers obtained in the previous step are pressed into a film and heated to 60°C in a vacuum oven for 3 hours for drying. Then, they are heated to 110-130°C in a muffle furnace and maintained for 1.5-3 hours for pre-oxidation to form an oxide film, which increases the intermolecular force, protects the fibers and removes impurities. Then, they are heated to 600-900°C in an inert atmosphere for carbonization to obtain Fe-doped MXene-CF film, i.e., MXene / phenolic carbon fiber film. Since phenolic fiber itself has no conductivity, it cannot be used to make sensors, but carbon fiber has a certain conductivity. Carbonization removes the internal oxides and loose structure to form purified carbon fibers.

[0011] In the above step (1), the molar ratio of formaldehyde to 5-hydroxyvaleraldehyde in the mixed aldehyde is 1:(0.05-0.3); the divalent metal catalyst is zinc acetate, stannous chloride or ferrous sulfate, and the acid catalyst is oxalic acid, citric acid or sulfurous acid.

[0012] In the above step (1), the mass ratio of the mixed phenol, the mixed aldehyde, the divalent metal catalyst and the acid catalyst is 1:(0.6-1):(0.01-0.025):(0.001-0.005).

[0013] In the above step (2), the mass ratio of MXene, ferric acetate and ethanol is 1:1:0.5; the mass ratio of mixed solution A and high-ortho-phenolic resin is (0.05-0.15):1; the mass ratio of amine curing agent and high-ortho-phenolic resin is 1% to 6%.

[0014] Furthermore, the amine curing agent is triethylamine, diisopropylamine or dimethylamine; MXene is Ti3C2T x 、Mo2CT x and Nb4C3T x At least one of .

[0015] In the above step (2), the spinning duct temperature of the dry spinning is 110-210° C., and the gas is nitrogen or argon.

[0016] In the above step (3), the inert atmosphere is one of nitrogen and argon or a mixture of the two gases.

[0017] MXene / phenolic carbon fiber film prepared by the above preparation method.

[0018] A thin film gas sensor includes the above-mentioned MXene / phenolic carbon fiber film and can be used to monitor TVOC gas.

[0019] The above-mentioned method for preparing the thin film type gas sensor is to coat the two ends of the above-prepared MXene / phenolic carbon fiber film with conductive glue as electrodes, and connect them to the test circuit through wires.

[0020] The conductive glue is conductive silver glue, conductive copper glue or conductive gold glue, and the conductive wire is copper wire, platinum wire or gold wire.

[0021] The beneficial effects produced by the present invention are:

[0022] (1) The present invention provides a novel method for preparing MXene / phenolic carbon fiber film, wherein MXene and Fe 3+Introduced into phenolic fiber precursor, and then cured and carbonized to prepare MXene-containing carbon film. Among them, the mixed phenol containing p-ethylphenol is used instead of phenol as raw material, which reduces the active sites of phenol in the raw materials and reduces cross-linking by avoiding the para position from participating in the polymerization reaction; 5-hydroxyvaleraldehyde improves the flexibility of the molecular chain and increases the spinnability on the one hand, and its tail hydroxyl group can form non-covalent bonds with metal iron ions and oxygen-containing functional groups on the surface of MXene, which is conducive to the uniform dispersion of metal iron ions and MXene, and increases the viscosity of the spinning solution, thereby facilitating spinning, which provides a way of thinking for the spinnability of MXene-based primary fibers.

[0023] (2) The phenolic fiber prepared by the present invention is made into a film, and with electrodes, it can be made into a thin film gas sensor, which has a simple structure, a low density relative to metal oxide materials, a certain degree of flexibility, and can work at room temperature; MXene and ferric acetate are introduced to enhance the gas-sensitive properties of phenolic-based carbon fibers. Specifically, the response value of the carbon fiber film to NO2 gas is increased by 3-4 times compared to that of the carbon fiber film without MXene added. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 It is an infrared graph of high-ortho-phenolic resin; the black curve in the figure is the infrared curve of the phenolic resin synthesized by phenol and tolualdehyde in the common method, and the red curve is the infrared curve of the high-ortho-phenolic resin synthesized by mixed phenol and mixed aldehyde in the present invention.

[0026] Figure 2 (a) The preparation flow chart of the sensor and (b) the actual picture of the produced MXene / CF carbonized film.

[0027] Figure 3 Scanning electron micrographs of MXene / phenolic carbon fiber film before (a) and after (b) carbonization.

[0028] Figure 4 This is the electron energy spectrum of the carbonized film.

[0029] Figure 5 This is the XRD diagram of the carbonized film. The red curve in the figure is the XRD spectrum of pure phenolic-based carbon fiber, and the black curve is the XRD spectrum of phenolic-based carbon fiber doped with MXene.

[0030] Figure 6 This is a selectivity test of the MXene / phenolic carbon fiber film-based gas sensor prepared by the present invention.

[0031] Figure 7 Response curves of the MXene / phenolic carbon fiber film prepared in Example 1 and the CF film-based gas sensor prepared in Comparative Example 1 to NO2.

[0032] Figure 8 This is the response recovery curve of the MXene / phenolic carbon fiber film-based gas sensor prepared in Example 1 to 10 ppm concentration of NO2.

[0033] Fig. 9 This is the response curve of the MXene / phenolic carbon fiber film-based gas sensor prepared in Example 2 to NO2.

[0034] Fig.10 This is the response curve of the MXene / phenolic carbon fiber film-based gas sensor prepared in Example 3 to NO2.

[0035] Fig.11 This is the response curve of the MXene / phenolic carbon fiber film-based gas sensor prepared in Comparative Example 2 to NO2. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] The preparation method of the MXene / phenolic carbon fiber film of this embodiment comprises the following steps:

[0039] (1) Mixed phenol (the mass ratio of phenol to p-ethylphenol is 9:1) and mixed aldehyde (the mass ratio of formaldehyde to 5-hydroxyvaleraldehyde is 1:0.05) are added into a reactor at a mass ratio of 1:0.6 to mixed phenol and aldehyde, and a mass ratio of 1:0.01 to zinc acetate. The mixed phenol and zinc acetate are added into a reactor and mixed evenly. The mixture is heated and stirred until boiling and the reaction is continued for 2 h. Oxalic acid (the mass ratio of mixed phenol to oxalic acid is 1:0.002) is then added and the reaction is continued for 1 h. The mixture is then heated to 105°C and distilled under reduced pressure to remove water and small molecular organic matter. The polymer remaining in the reactor is high ortho-phenolic resin, which is then naturally cooled to room temperature. Figure 1 This is the infrared image of the synthesized high-ortho phenolic resin. Compared with the general phenolic resin, the high-ortho phenolic resin synthesized by this method has an infrared range of 756 cm-1 There is a strong multi-CH2- (more than 4) vibration peak at the raw material, and 5-hydroxyvaleraldehyde introduces multiple methylene chains.

[0040] (2) MXene (Ti3C2T x ), ferric acetate and ethanol are mixed in a mass ratio of 1:1:0.5, and stirred evenly to obtain a mixed solution A; then the mixed solution A is added to the high-ortho-phenolic resin, and the mass ratio of the two is 0.1:1; heated to 78°C, stirred for reaction for 2 hours, and then triethylamine (the mass ratio of triethylamine to the high-ortho-phenolic resin is 4%) is added, and then the temperature is raised to 85°C and stirred for 1 hour before dry spinning to prepare the primary fiber. Among them, the air duct temperature in the dry spinning is 115°C, and the gas introduced is nitrogen.

[0041] (3) After the primary fibers obtained in step (2) are pressed into a film, the film is heated to 60°C in a vacuum furnace and maintained for 3 hours for drying, and then heated to 130°C in a muffle furnace and maintained for 2 hours for pre-oxidation treatment, and then heated to 700°C in an inert atmosphere for carbonization to obtain an Fe-doped MXene-CF film, i.e., a MXene / phenolic carbon fiber film. Figure 3 Scanning electron microscope images of MXene / phenolic carbon fiber film before (a) and after (b) carbonization. It can be seen from the figure that the fibrous materials are phenolic primary fibers (a) and carbon fibers (b), and the particulate matter is MXene agglomerates. Figure 4 This is the electron energy spectrum of the carbonized film, indicating that it contains Ti and Fe atoms, which are introduced by MXene and Fe ion doping, respectively. Figure 5 The XRD diagrams of the carbon fiber films prepared in Example 1 and Comparative Example 1 show that the XRD spectrum of the sample with added MXene (MXene / CF) has a diffraction peak of MXene relative to the sample without added (CF), indicating the successful doping of MXene.

[0042] The preparation method of the thin film gas sensor of this embodiment, the overall preparation flow chart is as follows Figure 2 (a), the steps are as follows:

[0043] The MXene / phenolic carbon fiber film prepared in this example is Figure 2 As shown in (b), it is light and flexible, can be bent, and cut into 2cm * The size of the film is 2 cm, and the conductive copper glue is used as the electrode to connect the copper wire in the test circuit to obtain a thin film gas sensor that can measure gas, which is recorded as MXene / CF.

[0044] Example 2

[0045] The preparation method of the MXene / phenolic carbon fiber film of this embodiment comprises the following steps:

[0046] (1) Mixed phenol (the mass ratio of phenol to p-ethylphenol is 9:1) and mixed aldehyde (the mass ratio of formaldehyde to 5-hydroxyvaleraldehyde is 1:0.05) are added into a reactor at a mass ratio of 1:0.6 to mixed phenol and aldehyde, and a mass ratio of 1:0.01 to zinc acetate. The mixed phenol and zinc acetate are added into a reactor and mixed evenly. The mixture is heated and stirred until boiling and the reaction is continued for 2 h. Oxalic acid (the mass ratio of mixed phenol to oxalic acid is 1:0.002) is then added and the reaction is continued for 1 h. The mixture is then heated to 105°C and distilled under reduced pressure to remove water and small molecular organic matter. The polymer remaining in the reactor is high ortho-phenolic resin, which is then naturally cooled to room temperature.

[0047] (2) MXene (Ti3C2T x ), ferric acetate and ethanol are mixed in a mass ratio of 1:1:0.5, and stirred evenly to obtain a mixed solution A; then the mixed solution A is added to the high-ortho-phenolic resin, and the mass ratio of the two is 0.05:1; heated to 78°C, stirred for reaction for 2 hours, and then triethylamine (the mass ratio of triethylamine to the high-ortho-phenolic resin is 4%) is added, and then the temperature is raised to 85°C and stirred for 1 hour before dry spinning to prepare the primary fiber. The air channel temperature in the dry spinning is 115°C, and the gas introduced is nitrogen.

[0048] (3) After the primary fibers obtained in step (2) are pressed into a film, the film is heated to 60°C in a vacuum furnace and maintained for 3 hours for drying, and then heated to 130°C in a muffle furnace and maintained for 2 hours for pre-oxidation treatment, and then heated to 700°C in an inert atmosphere for carbonization to obtain an Fe-doped MXene-CF film, i.e., a MXene / phenolic carbon fiber film.

[0049] The steps of preparing the thin film gas sensor of this embodiment are as follows:

[0050] The MXene / phenolic carbon fiber film prepared in this example was cut into 2 cm * The size of the film is 2 cm, and the copper wire is connected to the test circuit using conductive glue as the electrode to obtain a thin film gas sensor that can measure gas, which is recorded as MXene / CF-2.

[0051] Example 3

[0052] The preparation method of the MXene / phenolic carbon fiber film of this embodiment comprises the following steps:

[0053] (1) Mixed phenol (the mass ratio of phenol to p-ethylphenol is 9:1) and mixed aldehyde (the mass ratio of formaldehyde to 5-hydroxyvaleraldehyde is 1:0.05) are added into a reactor at a mass ratio of 1:0.6 to mixed phenol and aldehyde, and a mass ratio of 1:0.01 to zinc acetate. The mixed phenol and zinc acetate are added into a reactor and mixed evenly. The mixture is heated and stirred until boiling and the reaction is continued for 2 h. Oxalic acid (the mass ratio of mixed phenol to oxalic acid is 1:0.002) is then added and the reaction is continued for 1 h. The mixture is then heated to 105°C and distilled under reduced pressure to remove water and small molecular organic matter. The polymer remaining in the reactor is high ortho-phenolic resin, which is then naturally cooled to room temperature.

[0054] (2) MXene (Ti3C2T x ), ferric acetate and ethanol are mixed in a mass ratio of 1:1:0.5, and stirred evenly to obtain a mixed solution A; then the mixed solution A is added to the high-ortho-phenolic resin, and the mass ratio of the two is 0.07:1; heated to 78°C, stirred for reaction for 2 hours, and then triethylamine (the mass ratio of triethylamine to the high-ortho-phenolic resin is 4%) is added, and then the temperature is raised to 85°C and stirred for 1 hour before dry spinning to prepare the primary fiber. The air channel temperature in the dry spinning is 115°C, and the gas introduced is nitrogen.

[0055] (3) After the primary fibers obtained in step (2) are pressed into a film, the film is heated to 60°C in a vacuum furnace and maintained for 3 hours for drying, and then heated to 130°C in a muffle furnace and maintained for 2 hours for pre-oxidation treatment, and then heated to 700°C in an inert atmosphere for carbonization to obtain an Fe-doped MXene-CF film, i.e., a MXene / phenolic carbon fiber film.

[0056] The steps of preparing the thin film gas sensor of this embodiment are as follows:

[0057] The MXene / phenolic carbon fiber film prepared in this example was cut into 2 cm * The size of the film is 2 cm, and the copper wire is connected to the test circuit using conductive glue as the electrode to obtain a thin film gas sensor that can measure gas, which is recorded as MXene / CF-3.

[0058] Example 4

[0059] The preparation method of the MXene / phenolic carbon fiber film of this embodiment comprises the following steps:

[0060] (1) Mixed phenol (the mass ratio of phenol to p-ethylphenol is 8:1) and mixed aldehyde (the mass ratio of formaldehyde to 5-hydroxyvaleraldehyde is 1:0.15) are added into a reactor at a mass ratio of 1:0.8 for mixed phenol to mixed aldehyde and a mass ratio of 1:0.025 for mixed phenol to ferrous sulfate. The mixture is heated and stirred until boiling and the reaction is continued for 5 hours. Citric acid (the mass ratio of mixed phenol to citric acid is 1:0.001) is then added and the reaction is continued for 4 hours. The mixture is then heated to 105°C and distilled under reduced pressure to remove water and small molecular organic matter. The residual polymer in the reactor is high-ortho-phenolic resin, which is then naturally cooled to room temperature.

[0061] (2) MXene (Ti3C2T x ), ferric acetate and ethanol are mixed in a mass ratio of 1:1:0.5, and stirred evenly to obtain a mixed solution A; then the mixed solution A is added to the high-ortho-phenolic resin, and the mass ratio of the two is 0.15:1; heated to 75°C, stirred for reaction for 3.5 hours, and then dimethylamine (the mass ratio of dimethylamine to the high-ortho-phenolic resin is 6%) is added, and then the temperature is raised to 80°C and stirred for 1 hour, and then dry spinning is performed to prepare the primary fiber. The air duct temperature in the dry spinning is 110°C, and the gas introduced is nitrogen.

[0062] (3) After the primary fibers obtained in step (2) are pressed into a film, the film is heated to 60°C in a vacuum furnace and maintained for 3 hours for drying, and then heated to 110°C in a muffle furnace and maintained for 3 hours for pre-oxidation treatment, and then heated to 900°C in an inert atmosphere for carbonization to obtain an Fe-doped MXene-CF film, i.e., a MXene / phenolic carbon fiber film.

[0063] The steps of preparing the thin film gas sensor of this embodiment are as follows:

[0064] The MXene / phenolic carbon fiber film prepared in this example was cut into 2 cm * The size of the film is 2 cm, and the copper wire is connected to the test circuit using conductive glue as the electrode to obtain a thin film gas sensor that can measure gas, which is recorded as MXene / CF.

[0065] Example 5

[0066] The preparation method of the MXene / phenolic carbon fiber film of this embodiment comprises the following steps:

[0067] (1) Mixed phenol (the mass ratio of phenol to p-ethylphenol is 8.5:1) and mixed aldehyde (the mass ratio of formaldehyde to 5-hydroxyvaleraldehyde is 1:0.3) are added into a reactor at a mass ratio of 1:1 to mixed aldehyde and a mass ratio of 1:0.02 to stannous chloride. The mixed phenol and mixed aldehyde are added into a reactor and mixed evenly. The mixture is heated and stirred until boiling and the reaction is continued for 7 hours. Sulfurous acid (the mass ratio of mixed phenol to sulfurous acid is 1:0.005) is then added and the reaction is continued for 3 hours. The mixture is then heated to 105°C and distilled under reduced pressure to remove water and small molecular organic matter. The polymer remaining in the reactor is high-ortho-phenolic resin, which is then naturally cooled to room temperature.

[0068] (2) MXene (Ti3C2T x ), ferric acetate and ethanol are mixed in a mass ratio of 1:1:0.5, and stirred evenly to obtain a mixed solution A; then the mixed solution A is added to the high-ortho-phenolic resin, and the mass ratio of the two is 0.15:1; heated to 88°C, stirred for reaction for 2.5 hours, and then diisopropylamine (the mass ratio of diisopropylamine to the high-ortho-phenolic resin is 1%) is added, and then the temperature is raised to 92°C and stirred for 0.5 hours, and then dry spinning is performed to prepare the primary fiber. The air channel temperature in the dry spinning is 210°C, and the gas introduced is nitrogen.

[0069] (3) After the primary fibers obtained in step (2) are pressed into a film, the film is heated to 60°C in a vacuum furnace and maintained for 3 hours for drying, and then heated to 120°C in a muffle furnace and maintained for 1.5 hours for pre-oxidation treatment, and then heated to 600°C in an inert atmosphere for carbonization to obtain an Fe-doped MXene-CF film, i.e., a MXene / phenolic carbon fiber film.

[0070] The steps of preparing the thin film gas sensor of this embodiment are as follows:

[0071] The MXene / phenolic carbon fiber film prepared in this example was cut into 2 cm * The size of the film is 2 cm, and the copper wire is connected to the test circuit using conductive glue as the electrode to obtain a thin film gas sensor that can measure gas, which is recorded as MXene / CF.

[0072] Comparative Example 1

[0073] The preparation method of the phenolic-based carbon fiber film of this embodiment is different from that of Example 1 in that MXene and ferric acetate are not added to the high-ortho-phenolic film, and the steps are as follows:

[0074] (1) Mixed phenol (the mass ratio of phenol to p-ethylphenol is 9:1) and mixed aldehyde (the mass ratio of formaldehyde to 5-hydroxyvaleraldehyde is 1:0.05) are added into a reactor at a mass ratio of 1:0.6 to mixed aldehyde and a mass ratio of 1:0.01 to zinc acetate. The mixed phenol and zinc acetate are added into a reactor and mixed evenly. The mixture is heated and stirred until boiling and the reaction is continued for 2 hours. Oxalic acid (the mass ratio of mixed phenol to oxalic acid is 1:0.002) is then added and the reaction is continued for 1 hour. The mixture is then heated to 105°C and distilled under reduced pressure to remove water and small molecular organic matter. The polymer remaining in the reactor is high ortho-phenolic resin, which is then naturally cooled to room temperature.

[0075] (2) The high-ortho-phenolic resin is heated to 78° C., stirred for reaction for 2 h, and then triethylamine (the mass ratio of triethylamine to the high-ortho-phenolic resin is 4%) is added, and then the temperature is raised to 85° C. and stirred for 1 h before dry spinning to prepare spun fibers. The air channel temperature in the dry spinning process is 115° C., and the gas introduced is nitrogen.

[0076] (3) After the primary fibers obtained in step (2) are pressed into a film, the film is heated to 60°C in a vacuum furnace and maintained for 3 hours for drying, and then heated to 130°C in a muffle furnace and maintained for 2 hours for pre-oxidation treatment, and then heated to 700°C in an inert atmosphere for carbonization to obtain a phenolic-based carbon fiber film.

[0077] The steps of preparing the thin film gas sensor of this embodiment are as follows:

[0078] The phenolic carbon fiber film prepared in this example was cut into 2 cm * The size of the thin film is 2cm, and the copper wire is connected to the test circuit using conductive glue as the electrode to obtain a thin film gas sensor that can measure gas, denoted as CF.

[0079] Comparative Example 2

[0080] The preparation method of the MXene / phenolic carbon fiber film of this embodiment is different from that of Example 1 in that ferric acetate is not added, and the steps are as follows:

[0081] (1) Mixed phenol (the mass ratio of phenol to p-ethylphenol is 9:1) and mixed aldehyde (the mass ratio of formaldehyde to 5-hydroxyvaleraldehyde is 1:0.05) are added into a reactor at a mass ratio of 1:0.6 to mixed aldehyde and a mass ratio of 1:0.01 to zinc acetate. The mixed phenol and zinc acetate are added into a reactor and mixed evenly. The mixture is heated and stirred until boiling and the reaction is continued for 2 hours. Oxalic acid (the mass ratio of mixed phenol to oxalic acid is 1:0.002) is then added and the reaction is continued for 1 hour. The mixture is then heated to 105°C and distilled under reduced pressure to remove water and small molecular organic matter. The polymer remaining in the reactor is high ortho-phenolic resin, which is then naturally cooled to room temperature.

[0082] (2) MXene (Ti3C2T x) and ethanol in a mass ratio of 1:0.5, and stirred evenly to obtain a mixed solution A; then the mixed solution A is added to the high-ortho-phenolic resin in a mass ratio of 0.1:1; heated to 78°C, stirred for reaction for 2 hours, and then triethylamine (the mass ratio of triethylamine to the high-ortho-phenolic resin is 4%) is added, and then the temperature is raised to 85°C and stirred for 1 hour before dry spinning to prepare the nascent fiber. The air duct temperature in the dry spinning is 115°C, and the gas introduced is nitrogen.

[0083] (3) After the spun fibers obtained in step (2) are pressed into a film, the film is heated to 60°C in a vacuum furnace and maintained for 3 h for drying, and then heated to 130°C in a muffle furnace and maintained for 2 h for pre-oxidation, and then heated to 700°C in an inert atmosphere for carbonization to obtain a Fe-free MXene / CF film.

[0084] The preparation method of the thin film gas sensor of this comparative example comprises the following steps:

[0085] The Fe-free MXene / CF film prepared in this comparative example was cut into 2 cm * The size of the film is 2 cm, and the copper wire is connected to the test circuit using conductive glue as the electrode to obtain a thin film gas sensor that can measure gas, which is recorded as MXene / CF-4.

[0086] Implementation effect example

[0087] The performance tests were conducted on the thin film gas sensors prepared in Examples 1-3, Comparative Examples 1 and 2 of the present invention. All gas sensitivity tests were conducted at room temperature without additional heating. The results are as follows.

[0088] (1) Selectivity for gases

[0089] The sensor's response values ​​to 10ppm of several gases are as follows: Figure 6 As shown in the figure, the response value to NO2 is significantly greater than that to other gases, and the sensor shows excellent selectivity. As a two-dimensional material, MXene has excellent electron transport properties, and its surface has functional groups such as -OH, which have stronger binding ability with NO2 than reducing gases such as acetone, and is more conducive to chemical reactions on the sensor surface, thereby enhancing the surface electron transfer ability.

[0090] (2) Gas sensitivity

[0091] The thin film sensors prepared in Example 1 and Comparative Example 1 were placed in a test box, and the sensors were continuously tested for 1, 5, 10, 20 and 30 ppm NO2 gas. The response values ​​were as follows: Figure 7As shown in the MXene / CF and CF curves, the response value of comparative example 1 is significantly lower than the response value of the sensor made in Example 1 (MXene / CF) within the test concentration range. Specifically, the response values ​​of the MXene / CF-based sensor and the CF-based sensor to 30ppm NO2 are 5.1 and 1.2, respectively. The response and recovery time of the MXene / CF-based sensor to 10ppm NO2 gas are shown in Figure 8 As shown, they are 15s and 25s respectively, showing a faster response recovery.

[0092] The response curves of the MXene / CF film-based gas sensors prepared in Example 2 and Example 3 to 1, 5, 10, 20 and 30 ppm NO2 gas were tested respectively, and the response values ​​were as follows: Fig. 9 and Fig.10 As can be seen from the figure, the response values ​​of MXene / CF-2 and MXene / CF-3 to 30ppm NO2 are 1.8 and 2.2 respectively, which are lower than 5.1 of MXene / CF-1. In Comparative Example 2, the MXene / CF to which Fe was not added during the preparation process has a NO2 gas response curve as shown in Fig.11 As shown, the response value to 30ppm NO2 is 4.2, which is significantly smaller than that of the MXene / CF-based sensor with added Fe element (prepared in Example 1), indicating that the presence of a certain amount of Fe helps to improve the response performance. The reason is that the added Fe acts as an active site, increasing the chemical reaction activity of NO2 gas molecules on the sensor surface, thereby increasing the response value.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MXene / phenolic carbon fiber film, characterized in that: Here are the steps: (1) Mixing a mixed phenol consisting of phenol and p-ethylphenol, a mixed aldehyde consisting of formaldehyde and 5-hydroxyvaleraldehyde, and a divalent metal catalyst uniformly, heating and stirring until boiling, reacting for 2-7 hours, then adding an acid catalyst and continuing the reaction for 1-4 hours, and distilling under reduced pressure to obtain a high-ortho-phenolic resin; (2) adding MXene and ferric acetate to ethanol and stirring to obtain a mixed solution A; mixing the high-ortho-phenolic resin obtained in step (1) with the mixed solution A, heating and stirring to react, then adding an amine curing agent and heating to 80-92° C. to react for 0.5-1 h, and then dry spinning to obtain primary fibers; (3) The primary fibers obtained in step (2) are pressed into a film and dried, and then pre-oxidized and carbonized in sequence to obtain a Fe-doped MXene-CF film, i.e., a MXene / phenolic carbon fiber film.

2. The method for preparing the MXene / phenolic carbon fiber film according to claim 1, characterized in that: In the step (1), the mass ratio of phenol to p-ethylphenol in the mixed phenol is (8-9):1, and the molar ratio of formaldehyde to 5-hydroxyvaleraldehyde in the mixed aldehyde is 1:(0.05-0.3); the divalent metal catalyst is zinc acetate, stannous chloride or ferrous sulfate, and the acid catalyst is oxalic acid, citric acid or sulfurous acid.

3. The method for preparing the MXene / phenolic carbon fiber film according to claim 2, characterized in that: In the step (1), the mass ratio of the mixed phenol, the mixed aldehyde, the divalent metal catalyst and the acid catalyst is 1:(0.6-1):(0.01-0.025):(0.001-0.005).

4. The method for preparing the MXene / phenolic carbon fiber film according to claim 3, characterized in that: In the step (2), the mass ratio of MXene, ferric acetate and ethanol is 1:1:0.5; the mass ratio of the mixed solution A and the high-ortho-phenolic resin is (0.05-0.15):1; and the mass ratio of the amine curing agent and the high-ortho-phenolic resin is 1%-6%.

5. The method for preparing the MXene / phenolic carbon fiber film according to claim 4, characterized in that: In the step (2), the amine curing agent is triethylamine, diisopropylamine or dimethylamine; the temperature of the heating and stirring reaction is 75-88°C, and the reaction time is 2-3.5 hours; the spinning duct temperature of the dry spinning is 110-210°C, and the gas is nitrogen or argon.

6. The method for preparing the MXene / phenolic carbon fiber film according to claim 5, characterized in that: The pre-oxidation temperature in step (3) is 110-130°C and the time is 1.5-3h; the carbonization is carried out by heating to 600-900°C in an inert atmosphere.

7. A MXene / phenolic carbon fiber film prepared by the preparation method according to any one of claims 1 to 6.

8. A thin film gas sensor, characterized in that: The thin film gas sensor comprises the MXene / phenolic-based carbon fiber film of claim 7.

9. The method for preparing a thin film gas sensor according to claim 8, characterized in that: The two ends of the MXene / phenolic carbon fiber film of claim 7 are coated with conductive glue as electrodes, and connected to a test circuit through wires.

10. The method for preparing a thin film gas sensor according to claim 9, characterized in that: The conductive glue is conductive silver glue, conductive copper glue or conductive gold glue, and the conductive wire is copper wire, platinum wire or gold wire.